ECONOMETRIC ANALYSIS AND ASSESSMENT OF FACTORS AFFECTING THE EFFICIENCY OF AGRICULTURAL PRODUCTION - Vahid AMRAHOV; Elmir MAHMUDOV; Sabit ALIYEV; Sabina HAJIYEVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Taking into account that agricultural production interacts with various biological and natural processes, it is considered a fairly complex type of economic activity. The study of factors affecting the economic efficiency of agricultural production plays an important role in terms of efficient organization of production. The article presents the results of the analysis of the influence of the main factors on the gross output of the agricultural sector. The results obtained can be useful for both agricultural enterprises and private farmers, as well as government agencies for the optimal assessment of the state of agricultural policy and the development of the necessary conditions for the sustainable development of this industry. The main purpose of the article is to determine the level of influence of the most important factors on agricultural products, as well as forecasting these indicators for the prospective period. In the study of this issue in the article, methods of econometric analysis and modeling, economic and statistical analyzes, and the method of comparative analysis of indicators were used. For this, the literature was studied, including articles, scientific journals, textbooks. The empirical statistical data were taken from the State Statistics Committee of the Republic of Azerbaijan. The results of research by some scientists were also considered, as well as their methodologies were used in econometric analysis. At the end of the study, using the software, predictive indicators of the degree of influence of factors on agricultural products were determined.